The removal of phosphate ions from aqueous solution by fly ash, slag, ordinary Portland cement and related blends - Strydom, C.A. (Christiena Adriana) (University of Pretoria, 2013)
Thesis (PhD (Chemistry))--University of Pretoria, 2004.